A modified Steiner's analysis that does not require radiographic exposure of the cranial base. (6th December 2018) - Finn, Stephanie C.; Silver, Mathew T.; Canary, Benjamin; Kantarci, Alpdogan; Allareddy, Veerasathpurush; Katebi, Negin; Masoud, Mohamed I.
Structured Abstract: Objective: To correlate traditional Steiner's skeletal and dental measurements to similar measurements that use the eyes and natural head position as references instead of the cranial base. Setting and Sample: One hundred and fifty‐two lateral cephalometric radiographs (66 female and 86 male) from the Harvard Forsyth twin sample were included in the study based on record availability. Material and Methods: This was an observational study in which all cephalometric radiographs were traced and analysed using Steiner's cephalometric analysis. Each cephalogram was then altered to perform a similar analysis that uses the maximum convexity of the cornea together with natural head position as references instead of the cranial base. A Pearson product‐moment correlation coefficient was measured to determine the correlation between the conventional Steiner's analysis measurements and the novel measurements relying on the eyes and natural head position. Results: Steiner's cephalometric measurements of the jaws to each other, the divergency and the orientation of the incisors had a strong positive correlation with their counterparts that relied on true horizontal and/or the eyes ( P  < 0.001). Conclusion: The eyes and true horizontal can be used as alternatives to the cranial base when diagnosing the relationship between the jaws and the position and orientation of the teeth. Since the eyes and natural head position are identifiable without ionizing radiation, future research should focus on the use of radiographic exposures limited to the upper and lower jaws for orthodontic diagnosis and outcome assessment.